Synthesis of molluscicidal agent cyanolide a macrolactone from D-(-)-pantolactone - Hajare, Atul K.; Ravikumar, Velayutham; Khaleel, Shaik; Bhuniya, Debnath; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2011)
An efficient synthesis of potent molluscicidal agent cyanolide A, a glycosidic 16-membered macrolide, starting from D-(-)-pantolactone is reported. Highly stereoselective aldol, oxa-Michael addition, and Yamaguchi macrolactonization are the key steps in the present synthesis.